2023
DOI: 10.3390/brainsci13091334
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral S100B Protein Levels in Five Major Psychiatric Disorders: A Systematic Review

Tomasz Kozlowski,
Weronika Bargiel,
Maksymilian Grabarczyk
et al.

Abstract: Five major psychiatric disorders: schizophrenia, major depressive disorder, bipolar disorder, autistic spectrum disorder, and attention-deficit/hyperactivity disorder, show a shared genetic background and probably share common pathobiological mechanisms. S100B is a calcium-binding protein widely studied in psychiatric disorders as a potential biomarker. Our systematic review aimed to compare studies on peripheral S100B levels in five major psychiatric disorders with shared genetic backgrounds to reveal whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 130 publications
(511 reference statements)
0
0
0
Order By: Relevance
“…Indeed, post-mortem studies showed a reduced transcription of S100B in the PFC of MDD suicide completers [ 46 , 64 ] and a reduction in S100B+ cell density in the CA1 region of the hippocampus of MDD brains [ 65 ]. Although some studies described peripheral changes in serum S100B in MDD patients, this was not systematically found in MDD or across psychiatric disorders [ 65 , 66 , 67 , 68 ]. Although controversial results were reported between MDD severity and plasma/CSF S100B levels in different clinical studies [ 69 , 70 , 71 ], a meta-analysis showed significantly positive correlations between MDD severity and plasma/CSF S100B levels [ 67 ].…”
Section: Astroglial Dysfunction In Mood Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, post-mortem studies showed a reduced transcription of S100B in the PFC of MDD suicide completers [ 46 , 64 ] and a reduction in S100B+ cell density in the CA1 region of the hippocampus of MDD brains [ 65 ]. Although some studies described peripheral changes in serum S100B in MDD patients, this was not systematically found in MDD or across psychiatric disorders [ 65 , 66 , 67 , 68 ]. Although controversial results were reported between MDD severity and plasma/CSF S100B levels in different clinical studies [ 69 , 70 , 71 ], a meta-analysis showed significantly positive correlations between MDD severity and plasma/CSF S100B levels [ 67 ].…”
Section: Astroglial Dysfunction In Mood Disordersmentioning
confidence: 99%
“…Moreover, high baseline S100B in serum was associated with a greater response to antidepressant treatment [ 72 ]. These findings suggest that S100B could also be a potential peripheral biomarker for stress-related mood disorders or treatment response [ 68 , 73 ]. However, this statement has to be taken with caution, as both increased and decreased levels were reported in MDD.…”
Section: Astroglial Dysfunction In Mood Disordersmentioning
confidence: 99%
“…Moreover, the S100B protein is at the crossroads of several chronic pathological conditions of the nervous system; regardless of their origin, these disorders share aspects attributable to inflammation, including Alzheimer’s and Parkinson’s diseases, amyotrophic lateral sclerosis, multiple sclerosis, acute traumatic and vascular neural injury, and epilepsy. In experimental models of these diseases in general, overexpression/administration of S100B worsens the clinical presentation, while deletion/inactivation of the protein contributes to the improvement of symptoms of these diseases ( Kozlowski et al, 2023 ; Michetti et al, 2023 ).…”
Section: S100b Actionsmentioning
confidence: 99%